Crocin protects against smoke-induced chronic obstructive pulmonary disease by regulating AKT1 - Zhu, Yuehong; Jiang, Yuntao; Xu, Jieping; Yan, Sicheng; Ma, Zhihong (Frontiers in Pharmacology, 2026)
BackgroundChronic obstructive pulmonary disease (COPD) is an inflammatory airway disorder characterized by persistent airflow limitation and pathological features such as airway remodeling. Identifying molecular targets involved in airway epithelial dysfunction is crucial for developing COPD therapies. Crocin, a carotenoid glycoside from saffron (Crocus sativus L.), may exhibit pan-assay interference compounds (PAINS)-like properties owing to its conjugated polyene structure. This can lead to non-specific effects in vitro and complicate its pharmacological interpretation. Therefore, a multidimensional assessment strategy (network analysis + in vitro + in vivo) is essential to mitigate such limitations.MethodsWe first employed predictive strategies, including network analysis, to identify common targets of crocin and COPD. Protein-protein interaction (PPI) networks were constructed, and core targets were screened via topology analysis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to predict signaling pathways. Molecular docking and dynamics simulations were then used to assess the binding potential between crocin and the core targets. Finally, the function of crocin against COPD was evaluated using the Cellular Thermal Shift Assay (CETSA) in vitro and a cigarette smoke-induced mouse model in vivo.ResultsNetwork analysis predicted 243 common targets, from which 48 candidate targets were identified. GO and KEGG enrichment analyses suggested the PI3K-AKT signaling pathway as a potentially key mechanism. Among the top-ranked core targets, molecular docking indicated favorable binding energies between crocin and proteins such as ALB and AKT1, a finding further corroborated by molecular dynamics simulations. Subsequent CETSA suggested a direct interaction between crocin and AKT1. In vivo experiments demonstrated that crocin administration significantly alleviated lung injury and inflammation and reduced the p-AKT1/AKT1 ratio, consistent with network analysis and CETSA findings, suggesting the observed effects were not solely attributable to PAINS interference.ConclusionThese findings support the therapeutic potential of crocin in COPD through its anti-inflammatory activity and regulation of AKT1. Despite potential PAINS properties, the consistency across network, in vitro, and in vivo data strengthens the biological relevance of its observed effects.